2017
DOI: 10.1016/j.bjpt.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training improves aortic structure in Wistar rats

Abstract: HighlightsThere is aortic adaptation to resistance training in an experimental animal model.Resistance training promoted left ventricle concentric hypertrophy and improved aortic wall structure by increasing the density of elastic fibers and collagen fibers and increasing the thickness of collagen fibrils.Resistance training rats displayed aortic remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…The inner diameter decreased, and the wall thickness to diameter ratio increased in trained animals. Several observations have described lumen distension and thinner walls in vessels as effects of long-term physical exercise [11,12,[26][27][28][29], while others, similarly to us, have found thicker walls and decreased lumens [14,30,31]. A possible explanation is that different segments of the resistance artery network The elevated wall thickness to lumen diameter ratio may be advantageous in providing better control of the vascular lumen and segmental hemodynamic resistance.…”
Section: Similarities In Exercise-induced Heart and Coronary Adaptatisupporting
confidence: 48%
See 1 more Smart Citation
“…The inner diameter decreased, and the wall thickness to diameter ratio increased in trained animals. Several observations have described lumen distension and thinner walls in vessels as effects of long-term physical exercise [11,12,[26][27][28][29], while others, similarly to us, have found thicker walls and decreased lumens [14,30,31]. A possible explanation is that different segments of the resistance artery network The elevated wall thickness to lumen diameter ratio may be advantageous in providing better control of the vascular lumen and segmental hemodynamic resistance.…”
Section: Similarities In Exercise-induced Heart and Coronary Adaptatisupporting
confidence: 48%
“…The inner elastic membrane became thicker in the MEx animals than that in the MSe and FEx rats. Thickening of the elastic membranes as an effect of long-term exercise in the aorta has been described previously by Souza et al in male rats [31]. Following a moderate training program, Hanna et al described a reduction in the 'indentation' elastic moduli of coronary arterioles, with no change in the collagen/elastic tissue ratio.…”
Section: Sex Differences In the Exercise-induced Adaptation Of The Hementioning
confidence: 67%
“…Nineteen articles published data about the maximum load‐carrying tests protocol (Antonio‐Santos et al., 2016; Carbone et al., 2017; Chi et al., 2020; Deus et al., 2012; Domingos et al., 2012; Gil & Kim, 2015; Gomes, Borges, Rossi, Moura, & Medeiros, 2017; Grans et al., 2014; Hornberger & Farrar, 2004; Kwon et al, 2018; Lim et al, 2018; Mônico‐Neto et al, 2015; Neves et al, 2019; Padilha et al, 2017; Padilha et al., 2019; Perrilhão et al, 2019; Prestes et al, 2009; Souza et al., 2014; Souza et al, 2017). LRT presented a positive effect on the maximum load‐carrying capacity (16 studies, SMD 12.37, 95% CI [9.36, 15.37], p < .00001, I 2 = 90%, Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…De Souza et al, 67 , using the climbing a vertical ladder model, showed that RT promoted a 35% increase in CH, 17% in left ventricular thickness, 3% in left ventricular internal diameter and 27% in cross-sectional area of cardiomyocyte. Using the same model, Souza et al, 69 observed an increase in the aortic wall thickness, an increase elastic lamina and collagen fibers, and the thickness of collagen fibrils in trained rats. In this model, it was showed that RT reduced cardiac dysfunction in rats with diabetes 70 and in infarcted animals 71 .…”
Section: Cardiac Functionmentioning
confidence: 89%